PROPAGAÇÃO IN VITRO DE GERBERA JAMESONII BOLUS EX HOOK CV. APPELBLOESEM ATRAVÉS DE CAPÍTULOS JOVENS - BARBOSA, MARCIO HENRIQUE PEREIRA; Pinto, José Eduardo Brasil Pereira; Pinto, Cesar Augusto Brasil Pereira; Innecco, Renato (Revista Ceres, 2015)
.